The Risk of Cardiac Device-Related Infection in Bacteremic Patients Is Species Specific: Results of a 12-Year Prospective Cohort - Maskarinec, Stacey A (Open Forum Infect Dis, 2017)
BACKGROUND: The species-specific risk of cardiac device-related infection (CDRI) among bacteremic patients is incompletely understood. METHODS: We conducted a prospective cohort study of hospitalized patients from October 2002 to December 2014 with a cardiac device (CD) and either Staphylococcus aureus bacteremia (SAB) or Gram-negative bacteremia (GNB). Cardiac devices were defined as either prosthetic heart valves (PHVs), including valvular support rings, permanent pacemakers (PPMs)/automatic implantable cardioverter defibrillators (AICDs), or left ventricular assist devices (LVADs). RESULTS: During the study period, a total of 284 patients with ≥1 CD developed either SAB (n = 152 patients) or GNB (n = 132 patients). Among the 284 patients, 150 (52.8%) had PPMs/AICDs, 72 (25.4%) had PHVs, 4 (1.4%) had LVADs, and 58 (20.4%) had >1 device present. Overall, 54.6% of patients with SAB and 16.7% of patients with GNB met criteria for definite CDRI (P < .0001). Multivariable logistic regression analysis revealed that 3 bacterial species were associated with an increased risk for CDRI: Staphylococcus aureus (odds ratio [OR] = 5.57; 95% confidence interval [CI], 2.16–14.36), Pseudomonas aeruginosa (OR = 50.28; 95% CI, 4.16–606.93), and Serratia marcescens (OR = 7.75; 95% CI, 1.48–40.48). CONCLUSIONS: Risk of CDRI among patients with bacteremia varies by species. Cardiac device-related infection risk is highest in patients with bacteremia due to S aureus, P aeruginosa, or S marcescens. By contrast, it is lower in patients with bacteremia due to other species of Gram-negative bacilli. Patients with a CD who develop bacteremia due to either P aeruginosa or S marcescens should be considered for diagnostic imaging to evaluate for the presence of CDRI.